The role of third person pronouns in translation: a case study on “Detroit: Become Human” (Eurasian Journal of Philology Science and Education, 2025)
This research investigates the impact of pronoun translation, specifically “he”, “she” and “it” in the digital interactive entertainment software “Detroit: Become Human”. Pronouns play an important role in creating narrative dynamics and character perceptions in English, and thus their translation into languages that have different structures presents special challenges regarding gender specific pronouns.Therefore, the study seeks to investigate instances on how pronoun decisions are related to narrative depth. Since there are no gender-neutral pronouns in certain languages, the study addresses translation methods including direct equivalents, omitting pronouns or alternative strategies. The analysis of pronoun usage in English version and Russian/Kazakh translations compares how well and faithfully pronouns are translated with regard to cultural and linguistic differences. The study finally sheds light on how pronouns affect narrative building and how translation choices impact on the whole storytelling structure.The research advances the knowledge regarding pronouns as a distinct linguistic category, with a grammatical as well as semantic function. Theoretical discussions on the classification of pronouns and its role in narrative structures are extended. Offers practical examples of how translation choices can impact the reception of the story’s narrative. The research contains strategies for better handling of gender-neutral and context sensitive pronouns in translation. Methodology includes textual analysis, comparative analysis and case studies. The research reveals significant challenges in translation due to lack of gender-neutral options in Russian and Kazakh languages. Conclusion provides understanding of the importance of pronouns to the shaping of the narrative and character development of the story, pointing out that translation discrepancies can dilute narrative’s emotional and thematic depth. The findings can help improve localization practices ensuring that translations are faithful to the original narrative and cultural context.Keywords: translation, linguistic analysis, pronouns, pronoun dynamics, translation problems.